The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/diagnostics10080601
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Markers in Inflammatory Bowel Diseases: Systematic Review

Abstract: Precise diagnostic biomarker in inflammatory bowel diseases (IBD) is still missing. We conducted a comprehensive overview of oxidative stress markers (OSMs) as potential diagnostic, differential, progression, and prognostic markers in IBD. A Pubmed, Web of Knowledge, and Scopus search of original articles on OSMs in IBD, published between January 2000 and April 2020, was conducted. Out of 874 articles, 79 eligible studies were identified and used to prepare the interpretative synthesis. Antioxidants followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 121 publications
(414 reference statements)
0
46
0
4
Order By: Relevance
“…OS leads to the damage of the GI’s mucosal layer, which in turn stimulates immune response [ 4 ]. The imbalance between antioxidant systems and overproduction of ROS, generated mostly by phagocytic immune cells that infiltrate the mucosal tissue [ 2 , 3 , 4 ], disrupts cellular homeostasis, as it leads to cell malfunction and injury due to lipid, protein, carbohydrate and nucleic acid damage, thus accelerating and aggravating the inflammation [ 2 , 5 ]. OS, together with the following perpetuation of inflammatory reaction caused by overabundance of ROS, have been proposed as mechanisms involved in the onset, progression, and symptomatology of IBD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…OS leads to the damage of the GI’s mucosal layer, which in turn stimulates immune response [ 4 ]. The imbalance between antioxidant systems and overproduction of ROS, generated mostly by phagocytic immune cells that infiltrate the mucosal tissue [ 2 , 3 , 4 ], disrupts cellular homeostasis, as it leads to cell malfunction and injury due to lipid, protein, carbohydrate and nucleic acid damage, thus accelerating and aggravating the inflammation [ 2 , 5 ]. OS, together with the following perpetuation of inflammatory reaction caused by overabundance of ROS, have been proposed as mechanisms involved in the onset, progression, and symptomatology of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…OS, together with the following perpetuation of inflammatory reaction caused by overabundance of ROS, have been proposed as mechanisms involved in the onset, progression, and symptomatology of IBD. Antioxidant production is the first-line defense against ROS, however in a state of continuous OS those resources are diminished and IBD patients show reduced activity of main antioxidant systems and decreased detoxification [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α can not only ght tumors but also release in ammatory mediators and promote the necrosis of intestinal epithelial cells [14]. In addition, neutrophils produce excessive reactive oxygen species in patients with UC and subsequently attack and destroy key macromolecules, disrupt intracellular homeostasis, and cause oxidative damage in tissues, thus accelerating and prolonging in ammatory response [15]. The present study found that SOD activity decreased and MDA concentration increased in the DSS-treated group.…”
Section: Discussionmentioning
confidence: 54%
“…The oxidative damage of these macromolecules and the effects of pro-oxidants and antioxidants were studied over the past two decades as potential diagnostic, progression, and prognostic markers in CD, including in a recent systematic review on IBD and CD biomarkers by Krzystek-Korpacka [ 37 ]. Although a number of these markers show promise, they are mostly at the early research phase of discovery.…”
Section: Oxidative Stress In Crohn’s Diseasementioning
confidence: 99%